A Case Study on Mini Gas Cylinder Cluster : Evidence from India - Kapoor, Sandeep; Singh, Ajay (Prabandhan: Indian Journal of Management, 2023)
Access to cleaner cooking fuel is an essential factor that significantly impacts the living standards of human beings. Liquefied Petroleum Gas (LPG) is one of the clean sources of energy. The requirement of necessary documents and the completion of formal procedures for LPG and PNG connections deprive poor people, migrating workforce, and students who need readily available documents for LPG connections. Sensing this as an opportunity, some manufacturers started producing mini gas cylinders (MGC). The MGC cluster of Meerut, Uttar Pradesh, is a prominent manufacturing hub of such cylinders in India. The cluster had been involved in cylinder production for many years until 2013, when the government granted permission to sell 5kg LPG cylinders through retail outlets of oil distributors, with or without domestic pressure regulators. The research used the case study methodology to identify the problems and issues concerning the promising cluster. This case further corroborated the notion that government support and recognition are essential for the growth and sustenance of any business.